Skin Penetration of Corn Silk (Zea mays L.) Transdermal Patch on Wistar Mice Skin Using Franz Diffusion Cell - Alzahra, Dita Fatimah; Lestari, Ayu Diah; Haryadi, Elvan; Malau, Nur Aisyah; Risanli, Vio Agister; Fitria Apriani, Elsa Fitria Apriani (Universitas Airlangga, 2024)
Background: Corn silk (Zea mays L.) contains many active compounds, especially the flavonoid quercetin which has pharmacological activity as an antihyperlipidemic agent by reducing cholesterol and triglyceride levels in the body. Antihyperlipidemic treatment by oral route, such as statin drugs, has the disadvantage of experiencing a first-pass effect in the liver, which reduces the bioavailability of the drug. In addition to avoiding the first-pass effect, transdermal patches can improve patient compliance because they are easy to use. Objective: This study aims to optimize the transdermal patch formula of corn silk extract and test the penetration of the optimum formula by in vitro. Method: Optimization of the formula using the Regular Two-Level Factorial Design method on Design Expert®. This study used 2 factors, namely HPMC with a concentration of 3%-4% and PVP with a concentration of 1%-2%. The optimum formula obtained was subjected to in vitro penetration test using Franz diffusion cell. Results: Based on the results of factorial design analysis, the optimum formula of transdermal patches is at HPMC and PVP concentrations of 3.49% and 1% with moisture content, moisture uptake, percentage of elongation, and folding endurance respectively of 7.79%, 4.19%, 13.26% and 470.58 fold. The optimum formula of corn silk extract transdermal patch preparation also had an optimum percent cumulative amount of penetrated flavonoids of 96.06% and flux of 6.17 µg/cm2.hour at 3 hours. Conclusion: Transdermal patch dosage of corn silk extract with HPMC and PVP concentrations of 3.49% and 1% proved to have good characteristics and penetration rate.